Marketing Strategy of Samsung - Agarwal, Varsha (IJRAR, 2022)
This research paper provides an analysis of Samsung Korea’s largest chaebol group’s effective marketing strategy with which they have been able to dominate the global market. It covers aspects from the origins of Samsung to its present state and plans for the future as well as its marketing strategy such as its campaigns and how it utilizes the 4 Ps of marketing mix. It also mentions its growth in revenue and market in FY2020 and FY2021 due to these effective marketing strategies. The research mainly uses secondary data acquired from journals and websites. This research considers the global market. It also mentions what are the other products Samsung manufactures.
Keywords: Samsung; Smartphone; Marketing; Market; Korea